HIGH CHOLESTEROL LEVELS IN CORONARY HEART DISEASE WERE RECORDED IN THE MEDICAL POPULATION OF FERGHANA VALLEY (Global Conference on Medical and Health Sciences, 2026)
Ischemic heart disease (IHD) is one of the most common cardiovascular diseases worldwide. In this study, on the example of Fergana, Andijan and Namangan regions, epidemiological features of IHD, which depend on cholesterol levels in the population of doctors, were studied. The study involved 1,497 medical workers. The results showed that hypercholesterolemia is one of the important risk factors in IHD development. The high prevalence of hypercholesterolemia has been found to be associated with occupational stress and workload, especially in young and middle age groups. Also, the correlation between cholesterol levels and IHD has been statistically confirmed. The results obtained are important in strengthening preventive measures, reducing occupational risk factors and protecting the health of medical workers.
Keywords: Fergana,Namangan, Andijan regions, ischemic heart disease, population of medical workers, hypercholesterolemia, normaxolesterolemia.